The rhythm in the poetry of Anas Al-hajjar (Journal of Hama University, 2019)
This research is based on the study of rhythm in the poetry of Anas Al-Hajjar , a poet who knew his sense of humor , and the splendor of his words , in this books (Tears on Paper – The Magic of Femininity ),ALthough his poetic experience is new in time , he was able to impose himself strongly in the field of poetry ,hammering the pillars of it tent ,which spread its shadows over alrage area and the fans fulfilled his poetry. and the rhythm of several definitions , the vocal , musical, verbal and psychological. The rhythm must be studied in terms of its internal and external structure , and fit with the purpose the poet , and show the poet's interaction with his poetry , and his ability to convey his feeling and feeling to the recipient . Our poet,born in hama in 1975 , won the third place in the competition of the Ordinary Society  , he is known for his rich productions and creative casting , so he deserves our study and research . we hope that this modest research will illuminate an aspect of his poetry .